2018
DOI: 10.1093/mnras/sty2940
|View full text |Cite
|
Sign up to set email alerts
|

Radio broad-band visualization of global three-dimensional magnetohydrodynamical simulations of spiral galaxies – II. Faraday depolarization from 100 MHz to 10 GHz

Abstract: Observational study of galactic magnetic fields is limited by projected observables. Comparison with numerical simulations is helpful to understand the real structures, and observational visualization of numerical data is an important task. Machida et al. (2018) have reported Faraday depth maps obtained from numerical simulations. They showed that the relation between azimuthal angle and Faraday depth depends on the inclination angle. In this paper, we investigate 100 MHz to 10 GHz radio synchrotron emission f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Such a source is not suited to the study of WHIM's RM. We expect that it exhibits a strong depolarization feature caused by a turbulent magnetic field [49,50], so that we could discard it from the analysis.…”
Section: Intrinsic Rm and Cosmological Redshiftmentioning
confidence: 99%
“…Such a source is not suited to the study of WHIM's RM. We expect that it exhibits a strong depolarization feature caused by a turbulent magnetic field [49,50], so that we could discard it from the analysis.…”
Section: Intrinsic Rm and Cosmological Redshiftmentioning
confidence: 99%
“…Observational visualization is a powerful way of presenting information of the relation between the FD and the distribution of the physical gas and magnetic-field distributions. Machida et al (2018a) (Reference [6], hearafter Paper I) and Machida et al (2018b) (Reference [7], hearafter Paper II) reported a synthetic observational analysis of spiral galaxies using the spatial distribution of physical values used in numerical simulation. They assumed that the radio signal is a synchrotron emission from background radio sources.…”
Section: Introductionmentioning
confidence: 99%